Synthesis and Characterization of CdS/TiO2-Montmorillonite Nanocomposite with Enhanced Visible-Light Absorption. (20th January 2014) - Zhou, Feng-shan; Chen, Dai-mei; Cui, Bao-lin; Wang, Wei-heng
Abstract : Sodium montmorillonite (MMT) was chosen as the carrier; a serial of CdS/TiO2 -MMT nanocomposites with enhanced visible-light absorption ability was prepared by hydrothermal synthesis method combination with semiconductor compound modification method. The samples are characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and ultraviolet visible (UV-Vis) spectroscopy; the results showed that TiO2 and CdS nanoparticles were loaded on the surface of montmorillonite uniformly. N2 adsorption-desorption experiment showed that the specific surface area of TiO2 /montmorillonite nanocomposite made by this method can reach 200 m 2 /g and pore-size distribution was from 4 to 6 nm; UV-Vis showed that the recombination of CdS and TiO2 enhanced visible-light absorption ability of samples of TiO2 /montmorillonite and visible-light absorption ability increase with the increased of the adsorption of CdS.